Carbon Research - Wu, Fengchang; Li, Fangbai; Wang, Hailong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
The journal Carbon Research is an international multidisciplinary platform for communicating advances in fundamental and applied research on natural and engineered carbonaceous materials that are associated with ecological and environmental functions, energy generation, and global change. It is dedicated to serving as an innovative, efficient and professional platform for researchers in the field of carbon around the world to deliver findings from this rapidly expanding field of science. Carbon Research publishes articles related with an emphasis on, but not limited to the following: $1!#((B1$1!#) (BEngineered carbonaceous materials (e.g., biochar, bioplastics, nanomaterials, catalysts, etc.) and their applications to environmental remediation and restoration; $1!#((B2$1!#) (BNatural carbonaceous materials (e.g., humic substances, natural organic matter, cellulose, black carbon, etc.) and their biogeochemical cycling and ecological functions; $1!#((B3$1!#) (BCarbon and renewable energy generation; $1!#((B4$1!#) (BCarbon cycle, non-CO2 greenhouse gases and global change; $1!#((B5$1!#) (BCarbon neutrality and carbon-negative technologies; $1!#((B6$1!#)(BOther related novel sciences and technologies with global perspectives. .s
Keywords: Environment; Environmental engineering; Biotechnology; Bioremediation; Renewable energy sources; Cogeneration of electric power and heat; Fossil fuels; Environmental Sciences; Environmental Engineering/Biotechnology.; Renewable Energy; Fossil Fuel